The role of foreign languages in hospitality management - TZIORA, NEKTARIA; GIOVANIS, NIKOLAOS; PAPACHARALABOUS, CHARALABOS (International Journal of Language, Translation and Intercultural Communication, 2016)
The paper addresses the subject of foreign languages in hospitality management under the scope of their significance for the Greek hospitality industry and their role in the hospitality management education. Multilingualism offers a competitive advantage to both companies operating in the global hospitality market as well as people who pursue a career in it. The data presented herewith derives from a quantitative research that targeted managers of luxury hotels operating in Greece and hospitality management students. The key findings indicate a contradiction between theoretical acknowledgement of the importance of foreign languages in hospitality management and its practical promotion, particularly in regard to fluency in foreign languages, in service training initiatives and level of offered training courses. The paper aims to bridge the gap by showcasing up to date studies and presenting the special features of the Greek reality to promote further investigation of the field and to encourage specific action.